2019
DOI: 10.1108/bfj-01-2019-0067
|View full text |Cite
|
Sign up to set email alerts
|

Determinant factors of Indonesian people’s fish purchase intention

Abstract: PurposeThe purpose of this paper is to examine the determinant factors that influence the purchase intention of fish by Indonesians, especially in 14 provinces with low fish consumption rates.Design/methodology/approachThe survey was conducted with a total of 307 respondents in West Sumatra, Jambi, Bengkulu, Lampung, DKI Jakarta, West Java, Central Java, Special Region of Yogyakarta, East Java, Banten, Bali, West Nusa Tenggara, East Nusa Tenggara and West Borneo. The factors measured and analyzed are product, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
4
0
2
Order By: Relevance
“…Extant literature shows that the moderating role of genders, ages, marital status, and family structures has been conclusive in the TPB framework [28]. For instance, 234 respondents selected from Jammu and Kashmir were asked to fill out the personal information questionnaire.…”
Section: Hypothesis 8b Subjective Norm (Sn) Partly Mediates the Relat...mentioning
confidence: 99%
“…Extant literature shows that the moderating role of genders, ages, marital status, and family structures has been conclusive in the TPB framework [28]. For instance, 234 respondents selected from Jammu and Kashmir were asked to fill out the personal information questionnaire.…”
Section: Hypothesis 8b Subjective Norm (Sn) Partly Mediates the Relat...mentioning
confidence: 99%
“…However, product form may affect such attitudes; bones and smell were not perceived as negative factors in terms of attitudes towards dried fish consumption in Bangladesh [ 97 ], perhaps because of different food preparation and cooking techniques used for dried compared to fresh fish. Meanwhile, some articles have found that attitudes towards aquatic foods were influenced by perceptions of food safety, environmental concern, convenience and context, and socio-demographic characteristics [ 98 , 99 , 100 ]; however, having a positive attitude towards aquatic foods might not necessarily translate into eating more fish [ 101 , 102 ]. Finally, notable perceived behavioural control of aquatic food consumption includes affordability, convenience, and accessibility [ 91 , 92 , 96 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sikap adalah dampak evaluatif dari perasaan positif atau negatif yang ditampilkan oleh seorang individu pada suatu objek tertentu (Novita & Rowena, 2019). Pandangan konsumen tentang pentingnya penggunaan suatu teknologi dapat didefinisikan sebagai sikap konsumen.…”
Section: Dinning Attitudeunclassified
“…kota besar di Indonesia. Padahal Indonesia merupakan negara yang memiliki masyarakat dengan karakteristik suka mengonsumsi makanan sekaligus bersosialisasi (Novita & Rowena, 2019). Dengan adanya peraturan PPKM, masyarakat dianjurkan untuk tidak berpergian kecuali jika sangat diperlukan.…”
unclassified